Intention to adopt fintech services among entrepreneurs and student of entrepreneurship in Kuala Lumpur - Zaiton Osman; Phang Ing @ Grace; Izyanti Awang Razli; Wong Fu Rick (Asian Scholars Network, 2020)
Fintech is inevitable as the dynamic change in technology is continuously progressing. The pandemic of Covid-19 has forced entrepreneurs to change their norm of conducting business by inculcating fintech product and services as part of their business operation. This study investigates the intention to adopt fintech services among entrepreneurs and students of entrepreneurship in Kuala Lumpur. 213 data were collected from the respondent in Kuala Lumpur via purposive sampling and the data were analyse using SmartPls version 3.3.2. The findings showed that security concern, perceived enjoyment, government support have significant positive influence on the intention to adopt fintech services among entrepreneurs and students of entrepreneurship in Kuala Lumpur. The findings however showed that age does not play any moderation role in enhancing the relationship between security concern, perceived enjoyment, and government support towards the intention to adopt fintech services.